Relations between dermal sinus, aplasia cutis and collar sign. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
The cranial dermal sinus is related to an incomplete fusion of the neural tube level with the cephalic end; so originates a fistula that starting from the skin can end in the underlying soft tissue or cross the skull and connect the skin with the meningo-encephalic structures. The presence of the dermal sinus is often betrayed by the presence of a collar of thicker hairs (hair collar sign); however, this sign can also be found around other neoplasms (3). The presence of a gray, soft elastic plaque, sometimes surrounded by thicker hairs and often at the center of a salmon patch is more indicative of an embryonic malformation. However, the hair collar sign can also be found around membranous aplasia cutis (2); moreover, the latter may be preceded by a bullous stage where meningeal tissue can be histologically shown (1).